Growth trajectories in the strength of party identification: The legacy of autocratic regimes - Martin Kroh (Electoral Studies, 2014)
While some scholars interpret the frequently documented association between age and the strength of party identification as evidence of accumulated political learning, others stress the importance of critical life stages. Germany's turbulent last century, with its suspensions of democratic processes, provides the unique opportunity to empirically disentangle both effects and to also study the consequences of early experiences of autocratic regimes on later growth rates in partisan strength. Random growth curve models based on multi-cohort panel data emanating from the German Socio-Economic Panel show that the growth trajectory in the strength of party identification largely depends on the number of electoral experiences. Moreover, the analysis documents few differences in growth rates between individuals socialized in democratic versus autocratic regimes.
Additional information: NOTICE: This is the author's version of a work that was accepted for publication in Electoral Studies. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Electoral Studies ; 33 (2014), pp. 90-101 and is online available at http://dx.doi.org/10.1016/j.electstud.2013.06.013.
Keywords: 330; Growth curve models; Strength of party identification; Life-cycle; Germany; Political socialization; Democratization; Politische Partei; Statistische Methode; Deutschland; Soziale Gruppe